STUDY OF THE EFFECT OF SOME ALKALOIDS ON THE CONTRACTILE ACTIVITY OF AORTIC SMOOTH MUSCLE CELLS (World Bulletin of Public Health, 2024)
The aim of the work was to study the effect of 1-O-acetylkarakoline, a derivative of the diterpenoid alkaloid karakolin, isolated from the plant Aconitum karakolicum, on the contractile activity of smooth muscle cells (SMC) of the rat aorta. Karakolin has a pronounced antiarrhythmic effect, which is determined by the presence of specific functionally important groups in its structure [3]. Thus, the replacement of the OH-group at the carbon atom C-1 of the lycoketonin skeleton of Karakolin with an acetyl group (Fig. 1) leads to a significant increase in antiarrhythmic activity of 1-O-acetylkarakoline